A masquerader? Paecilomyces must be distinguished from Penicillium in fungal keratitis: a report of two contrasting cases. (18th August 2015) - Sheybani, Arsham; Nguyen, Alexander T; Harocopos, George; Lubniewski, Anthony J; Huang, Andrew J W
Abstract : We describe the clinical outcomes of two contrasting cases of fungal keratitis due to Paecilomyces spp. The first case involving a 58-year-old woman was complicated by an initial laboratory misidentification as Penicillium and consequently a delay in treatment with an optimised antifungal regimen. The patient had a protracted clinical course that required a total of four penetrating keratoplasties. However, an accurate diagnosis was promptly made in the second case, a 46-year-old woman, which resulted in a satisfactory outcome after penetrating keratoplasty. Our principal aim was to highlight a diagnostic challenge relating to the accurate microbial identification of Paecilomyces spp. This can be difficult given its morphological similarity to Pencillium, and confusion over the two genera has resulted in misdiagnoses reported previously. Our report aims to raise awareness of this potential laboratory misidentification, which can affect clinical decision-making in guiding antimicrobial therapy.